(untitled) (Bangladesh Agronomy Journal, 2021)
The experiment was conducted at the Research field of Agronomy Division, BARI, Joydebpur, Gazipur during rabi seasons of 2016-2017 and 2017-2018 to evaluate the effects of twig removal on yield and yield attributes, and extra benefit incurred due to removal of twig as a leafy vegetable in pea varieties. Treatments consisted of three varieties such as V1=Natore local, V2 = BARI Motorshuti-1 and V3= BARI Motor-1 and five twig removal variables, viz. T1= control (no removal), T2 = removal of 5 cm twig at 25 DAE, T3= removal of 7.5 cm twig at 25 DAE, T4=removal of 10 cm twig at 35 DAE, T5= removal of 12.5 cm twig at 35 DAE. Leafy vegetable yield varied among the varieties and twig removal variables. The highest leafy vegetable yield (778 and 975 kgha-1) over the years was recorded in BARI Motorshuti-1 when 12.5 cm twig removed at 35 days after emergence which was at par with BARI Motor-1 at the same cutting time and the same length. The maximum pod yield (9.15 t ha-1 and 9.52 t ha-1) was recorded in BARI Motorshuti-1 when 5cm twig removed at 25 days after emergence (DAE), which was statistically similar to the same variety with twig removal of 7.5 cm at 25 DAE. The highest gross return (Tk. 76522.00 ha-1), gross margin (Tk.48272.00 ha-1) and BCR (2.71) was recorded in BARI Motorshuti-1 when twig removed 5 cm at 25 DAE, which was similar to the same variety with 7.5 cm twig removed at 25 DAE. The result revealed that 5-7.5 cm twig removal at 25 DAE from the tip might be a profitable technique for pea (var. BARI Motorshuti-1) production for dual purpose as vegetables and pod yield. Bangladesh Agron. J. 2021, 24(1): 37-42